The Therapeutic Effect and In Vivo Assessment of Palmitoyl-GDPH on the Wound Healing Process - Nur Izzah Md Fadilah (Pharmaceutics, 2021)
The standard treatment of open wounds via the direct usage of therapeutic agents is not without limitations with respect to healing. Small peptides can create a favorable milieu for accelerating the healing of wounds. This study presents the potential of a novel fatty acid conjugated tetrapeptide (palmitic acid-glycine-aspartic acid-proline-histidine; Palmitoyl-GDPH) in alleviating wound healing. Tetracycline was employed as a standard control drug following its significance in wound healing including biologically active and antimicrobial effects. The peptide in liquid form was applied on to a 4 cm2 full thickness wound surgically induced at the dorsum of Sprague Dawley (SD) rats. The in vivo wound treatment with Palmitoyl-GDPH for eighteen days, histologically demonstrated an almost perfect healing exhibited by increased re-epithelialization, enhanced collagen deposition, and diminished scar formation compared to the controls. In addition, the well-developed epidermal-dermal junction and ultimate stimulation of hair follicle-growth in the Palmitoyl-GDPH treated group indicated the wound to have healed as functionally viable tissues. In general, the much lower hemogram values in the Palmitoyl-GDPH group indicated that the ongoing healing is en route to an earlier recovery. Additionally, the liver, kidney, and pancreas function biomarkers being within normal limits indicated the relatively non-toxic nature of Palmitoyl-GDPH at the used dosage. These results indisputably supported the great potential of this newly synthesized Palmitoyl-GDPH to be used as an effective therapeutic agent for wound healing (this actually means creating a new wound).